If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -7 = 23x + -15 Reorder the terms: -7 + 9x = 23x + -15 Reorder the terms: -7 + 9x = -15 + 23x Solving -7 + 9x = -15 + 23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23x' to each side of the equation. -7 + 9x + -23x = -15 + 23x + -23x Combine like terms: 9x + -23x = -14x -7 + -14x = -15 + 23x + -23x Combine like terms: 23x + -23x = 0 -7 + -14x = -15 + 0 -7 + -14x = -15 Add '7' to each side of the equation. -7 + 7 + -14x = -15 + 7 Combine like terms: -7 + 7 = 0 0 + -14x = -15 + 7 -14x = -15 + 7 Combine like terms: -15 + 7 = -8 -14x = -8 Divide each side by '-14'. x = 0.5714285714 Simplifying x = 0.5714285714
| v+914=-21 | | 11x-4=4(3x+2) | | 15x-9-7=x+5 | | z+15+5z+9=180 | | 3x^2-2x-10=7 | | 6x+7+4x+5=90 | | 3X-16=2X+18 | | x^2+6x-8=3x-7 | | 4d-36-24d=2-16-4d | | 28=-4y+2(y+4) | | 6-2(x-2)=3(x+3)-9 | | 2d+15=27 | | x+5-3+3x-3x+x^2+4+x=35 | | 8c-c-1=9 | | 3(24-x)=6-x | | 14c-11=3(2c+7) | | 7=3-2+4x | | 6(w-2)+3w=24 | | (A+b)+3= | | 25xsquared-16=0 | | 3a+45+2a-10=180 | | .75n-2=-.875n+32 | | 3X-16=2N+18 | | 11x+10x=12x | | 5sinx+4cosx=0 | | 8c-(c-1)=9 | | -5x^2+39x+8=0 | | -24=3v+4(v+8) | | 4y+y+1=7y | | 3x-8+x+26=180 | | 6x-5(x-7)=-10 | | -24=3v+4(4+8) |